2018
DOI: 10.1002/adsc.201701389
|View full text |Cite
|
Sign up to set email alerts
|

Nondirecting Group sp3 C−H Activation for Synthesis of Bibenzyls via Homo‐coupling as Catalyzed by Reduced Graphene Oxide Supported PtPd@Pt Porous Nanospheres

Abstract: The use of heterogeneous bimetallic Pd-based nanocatalyst for directing the inactivated sp 3 CÀH coupling has been scarcely explored. This work reported the formation of symmetrical CÀC bonds from the inactivated sp 3 CÀH bonds catalyzed by employing reduced graphene oxide supported PtPd@Pt porous nanospheres. The reaction of sp 3 CÀH activation proceeded under mild conditions without any solvent, ligand or directing group. It is a higher atom-, step-and cost-effectiveness strategy for developing heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Although the reductions of diarylalkenes and diarylalkynes provide means for the preparation of bibenzyl compounds 13 , 14 , homo-coupling strategies show superiority to access these compounds. For example, the homo-coupling of benzyl halides 15 , benzylmagnesium halides 16 , phenylacetic acids 17 , benzyl boronic acids 18 and methylbenzene derivatives 19 have been disclosed in recent years. However, these methods suffered from several drawbacks such as the tedious prefunctionalization steps, the use of moisture-sensitive organometallic reagents and the requirement of noble metals, which greatly limit their broad applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reductions of diarylalkenes and diarylalkynes provide means for the preparation of bibenzyl compounds 13 , 14 , homo-coupling strategies show superiority to access these compounds. For example, the homo-coupling of benzyl halides 15 , benzylmagnesium halides 16 , phenylacetic acids 17 , benzyl boronic acids 18 and methylbenzene derivatives 19 have been disclosed in recent years. However, these methods suffered from several drawbacks such as the tedious prefunctionalization steps, the use of moisture-sensitive organometallic reagents and the requirement of noble metals, which greatly limit their broad applicability.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a good result, we had to modify the photocatalyst, and found that the yield increased from 4% to 11% when Pd/g-C 3 N 4 was irradiated for 5 min in the presence of Na 2 CO 3 and water. These results indicate that the irradiating process can enhance the catalytic ability of Pd/g-C 3 N 4 , which is possibly due to that Pd 0 is the catalytically active species [47][48][49] , and such a process can result in an increase in the ratio of Pd 0 to Pd 2+ based on the characterization of catalyst. In addition, we observed the formation of hydrogen gas from the proton reduction that was unbeneficial for the reductive coupling, urging us to add a base to inhibit this competing reaction.…”
Section: Fig 1 Coupling Organic Reactions With Photocatalytic Half-reaction Of Water Splittingmentioning
confidence: 88%
“…However, it is desired to overcome this problem because a new use of water as the green reducing agent to enable the reductive transformations of organic substances can be developed by this way. In addition, the reductive coupling of aryl or alkyl halides is of great significance in modern organic synthesis [47][48][49][50][51][52][53][54][55][56] , which has prompted us to select this kind of reaction as the model reaction to make our idea come true. Encouraged by prior success in applying carbon nitride-supported transition metal (M/g-C 3 N 4 ) into photocatalytic water splitting, [57][58][59][60][61][62][63][64][65] we selected this kind of semiconductor to achieve our goals.…”
Section: Fig 1 Coupling Organic Reactions With Photocatalytic Half-reaction Of Water Splittingmentioning
confidence: 99%
“…Furthermore, the benzylic C−H bond in toluene is more feeble than arene C−H, which shows remarkable selectivity for C Sp3 –H activation over C Sp2 –H activation. Recently, the activation of C Sp3 –H bond of methylarenes for C–C and C–hetero bonds formation has received considerable attention . Few synthetic protocols have been reported for the formation of amides using methylarenes and amines, which would be a significant complement to the traditional C–N forming strategies (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%